The Correlation between Metacognitive Beliefs and Academic Performance in Students: Mediating Role of Learning Styles - Seyed Omid Sotoudeh Navroodi; Matina Bagheri Touchaee (Journal of Modern Psychology)
Objective: Academically successful students may expect higher performance in their next projects, volunteer work, and study sessions. Consequently, the primary emphasis of educational experts has always been elements impacting academic performance. This article examined the mediating effect of learning styles in the interaction between metacognitive viewpoints and students's academic achievement.Methods: This was descriptive, correlational study. Total number of female high school students in Astaneh Ashrafieh was 1,211. Random sampling enabled a cohort of 291 students to be chosen. Data were obtained with Academic Performance Questionnaire, Metacognitive Beliefs Questionnaire (MCQ) and Learning Style Orientation Measure (LSOM). Data analysis included structural equation modeling applied using SPSS-22 and Smart PLS 3.2.9 tools and correlation testing.Results: The findings revealed that indirectly, metacognitive views influenced academic performance by means of learning techniques. Moreover, academic performance revealed rather strong and unambiguous links between metacognitive perspectives and learning techniques (p <.05).Conclusion: Improved metacognitive views among students assist them to plan, define precise targets, track their learning activities and academic growth, and identify their strengths and flaws. Improving academic success and preventing academic failure depend on one focusing on the influence of metacognitive aspects and students' learning styles. At last, this study underlines how much learning techniques and metacognitive attitudes affect academic performance. The results reveal that by developing metacognitive abilities and appreciating various learning approaches, teachers may support their students in obtaining their academic goals quite efficiently.